Two-stage authentication and key agreement protocol for commuting in Internet of vehicles - ZHANG Haibo; YU Yi; WANG Dongyu; HE Xiaofan (Tongxin xuebao)
Aiming at the security and efficiency of commuter vehicles accessing services from road side unit (RSU) in Internet of vehicles (IoV), a two-stage authentication and key agreement protocol was proposed. In the initial authentication phase, the three independent session keys, negotiated among the vehicle, the RSU, and the trusted authority (TA), were utilized to safeguard the privacy of transmitted data between two entities from interception by third-party entities. In the fast authentication phase, the vehicle and RSU utilized the vehicle's travel schedule to reach the high-efficiency mutual-authentication. The vehicle anonymity and anonymous traceability were supported by the protocol, and the privacy leakage such as commuting routes was prevented. Additionally, the security of the protocol was proven by a random oracle. In a typical commuting scenario, the simulation results show that the protocol outcomes a reduction in computation overhead by 59.35% and communication overhead by 44.21%, compared to existing similar literature.